Der Brite als ein diskursiv erzeugter Gegenstand: Bedeutungsvarianten, Synonyme, Hyperonyme und Antonyme der lexikalischen Einheit Brite im Brexit-Diskurs der „Tageszeitung“ - Agnieszka Gaweł (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The cognitive linguistics bases its research on media discourse on the thesis that discourse central concepts have the status of mental objects which are construed in and experienced through discourse. In this paper, we present the application of one of the analytic tools developed within the cognitive ethnolinguistics, the cognitive definitions, in the reconstruction of the discourse central concept “Brite” („Briton“) in the Brexit discourse of the “Tageszeitung”. Relying on the assumption that a comprehensive analysis of the discourse construction of mental objects must refer to two types of categories: the discourse central conceptual domains and the linguistic correlates of the defined concept we focus our attention on the second class of categories: the synonyms, hypernyms, and antonyms of the lexical unit “Brite” („Briton“) in its diverse meaning and usage variants in Brexit discourse.